Epigenetic Inactivation of the BRCA1 Interactor SRBC and Resistance to Oxaliplatin in Colorectal Cancer - Moutinho, Catia; Martinez-Cardús, Anna; Santos, Cristina; Navarro-Pérez, Valentin; Martínez-Balibrea, Eva; Musulen, Eva; Carmona, F. Javier; Sartore-Bianchi, Andrea; Cassingena, Andrea; Siena, Salvatore; Elez, Elena; Tabernero, Josep; et al. (JNCI : Journal of the National Cancer Institute, 2014)
A major problem in cancer chemotherapy is the existence of primary resistance and/or the acquisition of secondary resistance. Many cellular defects contribute to chemoresistance, but epigenetic changes can also be a cause. A DNA methylation microarray was used to identify epigenetic differences in oxaliplatin-sensitive and -resistant colorectal cancer cells. The candidate gene SRBC was validated by single-locus DNA methylation and expression techniques. Transfection and short hairpin experiments were used to assess oxaliplatin sensitivity. Progression-free survival (PFS) and overall survival (OS) in metastasic colorectal cancer patients were explored with Kaplan-Meier and Cox regression analyses. All statistical tests were two-sided. We found that oxaliplatin resistance in colorectal cancer cells depends on the DNA methylation-associated inactivation of the BRCA1 interactor SRBC gene. SRBC overexpression or depletion gives rise to sensitivity or resistance to oxaliplatin, respectively. SRBC epigenetic inactivation occurred in primary tumors from a discovery cohort of colorectal cancer patients (29.8%; n = 39 of 131), where it predicted shorter PFS (hazard ratio [HR] = 1.83; 95% confidence interval [CI] = 1.15 to 2.92; log-rank P = .01), particularly in oxaliplatin-treated case subjects for which metastasis surgery was not indicated (HR = 1.96; 95% CI = 1.13 to 3.40; log-rank P = .01). In a validation cohort of unresectable colorectal tumors treated with oxaliplatin (n = 58), SRBC hypermethylation was also associated with shorter PFS (HR = 1.90; 95% CI = 1.01 to 3.60; log-rank P = .045). These results provide a basis for future clinical studies to validate SRBC hypermethylation as a predictive marker for oxaliplatin resistance in colorectal cancer.